Effect of moisture, bale type, and a preservative on alfalfa hay quality and feeding value - A. Laytimi; J. Arledge; C. Grimes; K. Bolsen (Kansas Agricultural Experiment Station Research Reports, 1986)
In the first of two alfalfa hay experiments, lambs fed small bale hays averaged 16% better gains and feed conversions than those fed large bale hays; Fresh Cut®-treated hay gave 9% better performance than untreated hays; and medium-moisture hays produced 12% faster and more efficient gains than low-moisture hays. In the second experiment, hay baled above 30% moisture had excessive heating, more discoloration and mold growth, higher storage losses, and lower dry matter and protein digestibilities compared with 15% moisture hay.
Keywords: Cattlemen' s Day; 1986; Kansas Agricultural Experiment Station contribution; no. 86-320-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 494; Beef; Moisture; Bale type; Preservative; Hay quality; Value